2020
DOI: 10.1128/aem.01113-20
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Drug-Induced Stress Responses Inhibit Formation of Escherichia coli Biofilms

Abstract: In most ecosystems, bacteria primarily exist as structured surface-associated biofilms that can be highly tolerant to antibiotics and thus represent an important health issue. Here we explored drug repurposing as a strategy to identify new antibiofilm compounds, screening over 1000 compounds from the Prestwick Chemical Library of approved drugs for specific activities that prevent biofilm formation by Escherichia coli. Most growth-inhibiting compounds, which include known antibacterial but also antiviral and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…It was suggested that efflux pumps are involved in the activation of the regulator of curli gene expression [ 141 ]. In E. coli , some drug-induced stresses repressed production of curli and thus repressed biofilm formation [ 147 ].…”
Section: Diverse Gut and Microbiota-derived Signals Induce Biofilm Formation In Commensal Bacteria And Enteropathogensmentioning
confidence: 99%
“…It was suggested that efflux pumps are involved in the activation of the regulator of curli gene expression [ 141 ]. In E. coli , some drug-induced stresses repressed production of curli and thus repressed biofilm formation [ 147 ].…”
Section: Diverse Gut and Microbiota-derived Signals Induce Biofilm Formation In Commensal Bacteria And Enteropathogensmentioning
confidence: 99%